(untitled) - Salter, Arthur (London, 1932)
This book is an attempt at a general map of the difficult country over which we have now to find our way, showing the obstructions by which it is encumbered, and, so far as possible, the practicable routes through it.
Keywords: Lịch sử kinh tế,Economic history